Uso de Bacillus sp. e Acibenzolar-S Metil como indutores de resistência ao crestamento bacteriano em soja (Pseudomonas savastanoi pv. glycinea) - Sbalcheiro, Cheila Cristina (2010)
The bacterial blight of soybean, induced by Pseudomonas savastanoi pv. glycinea (Psg), is responsible for significant crop damage and reductions in yield and grain quality. The disease is aggravated mainly because few cultivars and their resistance to the pathogen no efficient control measures. Induction of resistance in plants against pathogens is an alternative method of disease control and involves the activation of latent resistance in plant. This type of induction can be promoted by biotic and abiotic agents. The bacterium Bacillus sp. has been widely used as a biotic agent for induction resistance in several pathosystems with superior results compared to traditional methods of disease control. The abiotic agent acibenzolar-S-methyl (ASM), also provides the induction of resistance in several crops against a broad spectrum of pathogens. Thus, the biotic and abiotic agents were tested for power to control the pathogen in vitro and the sensitivity of Bacillus sp. the chemicals used in soybean crop for disease control. Soybean cultivars were tested for resistance to the pathogen and the agent biotic and phytotoxicity of ASM. The biotic and abiotic agents were tested in a greenhouse in the control of bacterial blight resistance induction and enzymatic changes caused in its application and inoculation of phytobacteria. The results of this study allowed to infer that agents Bacillus sp. and ASM did not promote significant control of Psg in vitro and showed no phytotoxicity in soybean. However, the disease was significantly controlled by biotic and abiotic agents in the greenhouse with the foliar application before inoculation with the pathogen. The application of Bacillus sp.and ASM, as well as inoculation with Psg promoted changes in the activity of peroxidase, β-1,3-glucanase, phenylalanine ammonia-lyase and polyphenoloxidase in soybean cultivars resistant and susceptible to bacterial blight